2021
DOI: 10.1007/s40618-021-01562-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term remission of acromegaly after somatostatin analogues withdrawal: a single-centre experience

Abstract: Purpose A long-lasting remission of acromegaly after somatostatin analogues (SAs) withdrawal has been described in some series. Our aim was to update the disease evolution after SAs withdrawal in a cohort of acromegalic patients. Methods We retrospectively evaluated 21 acromegalic patients previously included in a multicentre study (Ronchi et al. 2008), updating data at the last follow-up. We added further 8 patients selected for SAs withdrawal between 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our case combined with the available literature proved that long‐term remission was expected in a subgroup of acromegalic patients, thus challenging the previous concepts. Similarly, a recent study on first‐generation SSAs indicated a similar percentage of patients (21% or 6/29) with persistent remission, identified as having constantly “safe” GH and normal IGF‐1 concentrations and stable neuroradiological imaging after the discontinuation of medication 18 . Periodic treatment discontinuation is important given that at least a subset of patients with acromegaly will achieve long‐term remission, and they will be expected to acquire an improved quality of life through elimination of medication‐related adverse effects.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Our case combined with the available literature proved that long‐term remission was expected in a subgroup of acromegalic patients, thus challenging the previous concepts. Similarly, a recent study on first‐generation SSAs indicated a similar percentage of patients (21% or 6/29) with persistent remission, identified as having constantly “safe” GH and normal IGF‐1 concentrations and stable neuroradiological imaging after the discontinuation of medication 18 . Periodic treatment discontinuation is important given that at least a subset of patients with acromegaly will achieve long‐term remission, and they will be expected to acquire an improved quality of life through elimination of medication‐related adverse effects.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, the GH‐secreting pituitary adenoma had disappeared before the discontinuation of medication in our patient who obtained perpetual remission. Nevertheless, Sala et al 18 and Hatipoglu et al 8 reported no radiological differences between the patients achieving long‐term remission and those relapsing after treatment withdrawal. This needs to be confirmed in clinical practice, when SSAs withdrawal is possible, and in larger prospective studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation